2023
DOI: 10.1038/s43247-023-01104-w
|View full text |Cite
|
Sign up to set email alerts
|

Solutions for recycling emerging wind turbine blade waste in China are not yet effective

Juhua Yang,
Fanran Meng,
Lixiao Zhang
et al.

Abstract: Wind power supply chains are evolving as markets expand to reach climate goals. With the largest installed wind power capacity globally, China must deal with increasing composite turbine waste and anticipate its associated costs. Here we predict the quantity and composition of wind turbine blade waste based on historic deployment. A high-resolution database containing 14 turbine capacities (150–5500 kilowatts) was compiled based on 104 turbine models. The environmental and financial costs of waste treatment op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This work has shown, however, that while using GRP as feedstock in EfW facilities can reduce landfill burden, this results in significantly higher GWP than simply landfilling. This has also been shown to be the case in North America [13] and China [14]. Given the UK (and other global) commitments to Net Zero 2050, incinerating GRP waste for energy alone must also be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work has shown, however, that while using GRP as feedstock in EfW facilities can reduce landfill burden, this results in significantly higher GWP than simply landfilling. This has also been shown to be the case in North America [13] and China [14]. Given the UK (and other global) commitments to Net Zero 2050, incinerating GRP waste for energy alone must also be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has been recently devoted to the development of composite recycling techniques, which have led to various recycling strategies, each at different Technology Readiness Levels (TRL). In recent years these technologies have been widely reviewed in terms of the methods under development [6,7], TRL [8], recovered material properties [9,10], ongoing challenges [11], optimisation pathways [12], and environmental impacts [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the potential for upscaling, the process remains energy-intensive, and the utilization of rare and scarce ruthenium as a catalyst makes the process expensive. A study addressing different methods for recycling WTBs in China─ the global leader in production and installed wind power capacity, highlights the importance of promoting recycling technologies, particularly focusing to extract the maximum value from fibers at a low cost 21 . Additionally, it was found that the optimal management of WTBs and its associated environmental impacts exhibit variation at the regional level, primarily influenced by the characteristics of local energy systems.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found that the optimal management of WTBs and its associated environmental impacts exhibit variation at the regional level, primarily influenced by the characteristics of local energy systems. Paradoxically, it was found that employing mechanical recycling followed by landfill disposal of residual materials in WTBs yields the lowest GHG emission impact among all recycling processes; however, the current regulations in China prohibit the disposal of solid waste through this method 21 . This underscores the importance of examining regional dynamics beyond the national level and underscores the need to review existing policies when crafting strategies for EoL wind turbines.…”
Section: Discussionmentioning
confidence: 99%